SAFE BEHAVIOR AS BASIS FOR STRESS TOLERANCE IN ATHLETES - Krutko, I.S.; Popova, N.V.; Bauer, I.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the engineering students’ attitudes to physical education and safe behavior with their competitive spirit and stress tolerance building benefits. Methods and structure of the study. The study of youth safe behavior and the relevant addiction control competences was run in Yekaterinburg in 2021. We sampled for the study the 1-2-year Ural Federal University bachelor sporting students of different specialties. First we run a questionnaire survey of the group safe behavior with the safe behavior analysis and classification to find the key socio-didactic problems of the safe behavior styling service (February 2021, n=146). The survey was followed by a viability rating psychological tests of a vulnerable subsample (n=60) that reported high-risk experiences they failed to effectively address. Results and conclusion. The study tested the sporting students sample low on the viability/ stress tolerance resource scales, with the stress coping strategies dominated by confrontational coping styles. The safe behavior style in the sporting students perceptions was found centered on the personality component and operational component. Such primary safe behavior style provides a basis for an integrated proactive safe behavior style and safe-behavior-based stress tolerance building service for young people. The study has contributed to the Stress Tolerance Building Project with its Viability Laboratory that offers special mental conditioning games to help trainees master the safe behavior style formation basics by the high-risk situations and stress coping behavior modeling and testing role games.